2019
DOI: 10.18483/ijsci.2032
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of the Effects of some Herbal Drugs on the Heamatological and Biochemical Parameter of Winster Albino Rats

Abstract: The safety level of herbal drugs especially those that are produced in developing countries are of great concern to all stakeholders in health care system. The effects of aqueous extracts of five randomly selected locally produced antimalarial herbal drugs in South Western Nigeria on the biochemical and heamatological parameters of the blood of wistar albino rats were examined. Thirty three rats of both sex and of weight range 180-200g were acclimatized for two weeks, after which they were randomly distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
0
1
Order By: Relevance
“…The susceptibility of the fungi strains to synthesized AgNPs was in the order of Candida tropicalis > Aspergillus flaws > Fusarium oxysperium > Candida albican. The antifungal activity of this study was found to be higher than that obtained from the previous studies [46][47][48][49][50][51]. The higher antifungal potency…”
Section: Antifungal Activity Of Synthesized Agnpscontrasting
confidence: 79%
“…The susceptibility of the fungi strains to synthesized AgNPs was in the order of Candida tropicalis > Aspergillus flaws > Fusarium oxysperium > Candida albican. The antifungal activity of this study was found to be higher than that obtained from the previous studies [46][47][48][49][50][51]. The higher antifungal potency…”
Section: Antifungal Activity Of Synthesized Agnpscontrasting
confidence: 79%